Konektivitas Pada Area Rumah Susun Harapan Jaya di Kota Pontianak - Mutia Muyasarah; Ahmad Sarwadi (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Pontianak City has six housing that have been built and inhabited. It is interesting to see the use of the housing by the occupants. There is a fact that the circulation route of Harapan Jaya Housing is not fully utilized according to plan. The purpose of this research is to reveal which of these circulation pathways are used by the occupants and identifying potential circulation pathways. The research focuses on circulation issues, which connectivity between areas has succeeded in supporting the occupants’s activities. The data collection method was carried out by field observations and interviews with the occupants to confirm the observations results. The analysis method uses depthmapX-space syntax software with an axial map to determine the level of connectivity and integration that occurs. This study also simulated the addition of alternative circulation pathways. The results indicate that the addition of circulation paths can improve connectivity within the housing area. Efficient and functional connectivity in housing can use two models of circulation path, namely linear or grid.